PACCT: an intervention to increase clinical trial invitations for Black and White men with cancer: Presenter(s): Lauren Hamel, Wayne State University/Karmanos Cancer Institute, United States. (April 2023) - Senft, Nicole; Kim, Seongho; Jang, Hyejeong; Manning, Mark; Foster-Moore, Tanina; Baidoun, Fatmeh; Carducci, Michael; Lansey, Dina; Heath, Elisabeth; Eggly, Susan
Abstract : Background: Cancer clinical trial enrollment rates are low, with Black individuals especially underrepresented. We tested Partnering Around Cancer Clinical Trials (PACCT), an intervention designed to improve patient-physician communication and increase trial invitations among Black and White men with prostate cancer. Methods: Black and White men with prostate cancer and their physicians were invited to participate. Patients were tracked<two years for trial eligibility, with eligible patients randomized to usual care or intervention. Intervention patients received a brochure promoting patient-physician partnerships and a trials-focused Question Prompt List to encourage them to participate actively in clinic visits, such as by asking questions. Patient-physician visits were video-recorded. After the visits, communication (i.e., patient active participation and physician patient-centered communication) was assessed via patient self-report and observer ratings of video-recordings. Medical chart abstractions determined trial invitations. Univariable logistic mixed-effects models nesting patients within physicians tested intervention effects by race on communication and trial invitation. Findings: Among 199 participants (91 Black; 108 White), 22% (n=44; 20 Black, 24 White) became eligible for a trial and received the intervention (n=19) or usual care (n=25). Regarding communication, Black intervention patients reported participating more actively than those in usual care (difference=0.41, 95% CI -0.27-1.08), while White intervention patients reported participating less actively than those in usual care (difference=-0.34, 95% CI -0.72-0.05). No differences in observer ratings of active participation or self-report or observer ratings of physician communication were found. Regarding trial invitations, findings, although nonsignificant, showed more intervention patients (74%) than usual care patients (60%) received invitations (logOR=1.97, 95% CI -0.30 to 4.24), with Black intervention patients having higher odds of receiving invitations (80%) than White intervention patients (67%) (logOR=3.84, 95% CI -0.92 to 8.59 vs. logOR=-0.14, 95% CI -4.61 to 4.50). Discussion: The PACCT intervention showed promise in increasing Black patients' active participation and clinical trial invitations.